Haramiyidan mammals from the Middle Jurassic of Western Siberia, Russia. Part 1: Shenshouidae and Maiopatagium. Issue 4 (4th July 2019) - Averianov, Alexander O.; Martin, Thomas; Lopatin, Alexey V.; Schultz, Julia A.; Schellhorn, Rico; Krasnolutskii, Sergei; Skutschas, Pavel; Ivantsov, Stepan
ABSTRACT: Three new euharamiyidan taxa are described based on isolated teeth from the Middle Jurassic (Bathonian) Itat Formation of the Berezovsk coal mine in Krasnoyarsk Territory, Western Siberia, Russia. The newly erected Sharypovoia, gen. nov., is referred to the Shenshouidae based on a premolariform p4, in which the main cusp and basined heel are surrounded by two rows of cusps. Attributed upper molars have the main labial cusps A1 and A2 connected by a ridge that lacks small additional cusps. In the smaller species S. arimasporum, sp. nov., there are one to two additional cusps mesial to cusp A2, whereas the larger S. magna, sp. nov., lacks these additional cusps. Maiopatagium sibiricum, sp. nov. (Euharamiyida incertae sedis), is similar to M. furculiferum from the Late Jurassic Yanliao Biota of northeastern China in having coalesced crest-like lingual cusps and an open occlusal furrow medially on the upper cheek teeth. Sineleutherus uyguricus from the Upper Jurassic (Oxfordian) Qigu Formation in Xinjiang, China, is restricted to the holotype only, a lower molar, and referred to the Arboroharamiyidae. The previously published sample of ' Sineleutherus ' issedonicus from the Itat Formation represents a mixture of shenshouid and arboroharamiyid euharamiyidan taxa, and the holotype of that species, a lower molar, should be referred to a new genus of Arboroharamiyidae. The Asiatic euharamiyidan taxa are referable either to Shenshouidae or Arboroharamiyidae, but not to Eleutherodontidae.